How are they doing? Listening as fathers of children with autism spectrum disorder compare themselves to fathers of children who are typically developing. (April 2016) - Cheuk, Samantha; Lashewicz, Bonnie
The growing prevalence of autism spectrum disorder is accompanied by ongoing efforts to understand and support parents in the face of challenges related to their child's autism spectrum disorder. Although fathers are increasingly hands-on in raising children, research focus on parenting children with autism spectrum disorder continues to be skewed toward experiences of mothers. Our purpose in this article is to contribute understandings of how fathers of children with autism spectrum disorder perceive themselves to be managing, and we undertake this by examining comparisons fathers of children with autism spectrum disorder make between their parenting experiences and experiences of fathers of typically developing children. A purposive sample of 28 fathers of children (aged 2–13 years) with autism spectrum disorder living in an urban center in Western Canada participated in in-depth interviews about their parenting successes and challenges. We found fathers speak of universal fathering experiences yet articulate their own sense of loss and efforts to come to terms with unanticipated demands associated with autism spectrum disorder. Fathers of children with autism spectrum disorder feel "pangs of jealousy" toward fathers of typically developing children, yet they are keenly attentive to their own child's development and convey a sense of gratitude for their child's capabilities and personality amidst an appreciation for trials and triumphs of fathering in general and fathering a child with autism spectrum disorder in particular.